Postać wszechświatowego człowieka w twórczości reżysera, scenarzysty i muzyka Michaiła Miesteckiego - Szubin, Roman (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2019)
The article is devoted to the study of the concept and image of the one-man (rus. mirovoj chelovek). Mikhail Mestetsky – a screenwriter, a director, a musician, the founder and frontman of the group Shklovsky. His work is permeated with anarchic and revolutionary motifs of destruction and provocation. However, along with the aesthetics of destruction, there is a tendency towards collective behavior, the essentialization of the collective. The group, the detachment, the team, the union, and the sect are the favorite categories of Mestetsky's poetics. The identification of „all as one” in the category of the one-man (Wardan Hayrapetyan), collective body occurs in the film Rag Union (2015). The main plot of Mestetsky is set against this background – the self-education of personality and the character formation.